Correlation of cardiopulmonary exercise testing parameters with quality of life in stable COPD patients - Mirdamadi, Mahsa; Rahimi, Besharat; Safavi, Enayat; Abtahi, Hamidreza; Peiman, Soheil (Journal of Thoracic Disease, 2016)
Background: The precise head to head relationships between Cardio-pulmonary exercise testing (CPET) parameters and patients’ daily symptoms/activities and the disease social/emotional impact are less well defined. In this study, the correlation of COPD daily symptoms and quality of life [assessed by St. George’s Respiratory Questionnaire (SGRQ)] and COPD severity index (BODE-index) with CPET parameters were investigated. Methods: Symptom-limited CPET was performed in 37 consecutive COPD (GOLD I-III) subjects during non-exacerbation phase. The SGRQ was also completed by each patient. Results: SGRQ-score correlated negatively with FEV1 (r=−0.49, P